Speech Act, Cooperative Principle, and Politeness Strategies of East Java Governor on Ganjar Pranowo YouTube Channel - Sumarlam (TALENTA Publisher, 2022)
This study was driven by the significance of revealing public figures' speech acts, cooperative principles, and politeness strategies in creating effective interactions and communication with speech partners. This study involved three areas of study, speech acts, cooperative principles, and politeness strategies. The data were in the form of a dialogue between the speaker (Ganjar Pranowo) and the speech partners (economic actors, arts and culture, and health), in which aspects of speech acts, the implementation of the cooperative principles, and the selection of politeness strategies and their contexts are explored. The data were obtained from Ganjar Pranowo's YouTube channel in three domains by watching, downloading YouTube, and using orthographic recording and transcription techniques. The data were then analyzed using pragmatic and contextual matching technique, and Spradely's [1] ethnographic approach modified by Santosa [2]. The results and discussion of the study concluded that (1) the most frequently used speech acts by the speaker (GP) and speech partners (economic actors, artists, and health practitioners and their patients) were directive and representative speech acts. (2) The tact and generosity maxims were observed by GP in interacting and communicating with speech partners. (3) Politeness strategies used by GP to increase social interactions and successful communication with speech partners are positive politeness strategies with direct strategies, supported by humorous sub-strategies, and giving attention in financial and non-financial forms.